Quick and Easy : Salads and Breads with Style (Food, Family & Friends Cookbook series) / Edie Hand, Darlene Real, Debra Lustrea - Hand, Edie
These innovative cookbooks are devoted to celebrating wonderful food and a contemporary sense of style on a budget. Provided are recipes for delicious and easy holiday treats, entrees, and salads and breads that take fewer than 20 minutes to prepare and present with flair. Appropriate for both novice and experienced cooks, all of these recipes use ingredients commonly found on supermarket shelves. Each recipe is accompanied by nutritional information and diabetic food exchanges.